Role of Constitutional Court in consolidating democracy in Indonesia - Satriawan, Iwan (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2017)
The principal aim of this research is to evaluate the role of the Constitutional Court in relation to consolidation of democracy in Indonesia by examining its decisions and the effect that the decisions made. This qualitative research uses doctrinal legal approach as well as examining application of law. It transpires that the Constitutional Court, through its decision, has become an important institution in supporting the quality of elections. Through its decisions, the Constitutional Court has played a significant role in protecting the fundamental rights of citizens through the judicial review of election acts which secure the quality of democracy. The Constitutional Court has also contributed significantly to the creation of a more conducive political situation in the elections. It is also observed that the Constitutional Court has successfully contributed to the working of the general elections in 2004 and 2009 in securing the fundamental rights of citizens in the general elections and settling of disputes over the result of general elections. In addition, the Constitutional Court has also created a more conducive political situation and contributed significantly to the process of consolidating local democracy in Indonesia. In spite of these achievements, it is found the Constitutional Court has not played a significant role in settling disputes concerning constitutional authority among state organs. This study ends with some recommendations which can be made for an enhanced role of the Constitutional Court.such as by letting the MPR has to take the initiative to amend the 1945 Constitution on two points, firstly, to re-design the structure and authority of the Constitutional Court and secondly, the DPR needs to amend the Constitutional Court Act so as to resolve the current issues of the Constitutional Court, such as more independence of the justices, better supervision to the justices, better recruitment of justices and stronger support of the justices.